Unveiling the Nexus of Distribution Personalization and Content Decentralization: Exploring Brand Recall among Gen Z in Region III, Philippines - Campos, Josephine Diana S; Campos, Jofrey R (International Journal of Entrepreneurship, Business and Creative Economy, 2024)
The study emphasized the pivotal role of distribution personalization, mediated by content decentralization, in influencing brand recall among Gen Z consumers, highlighting the importance of advanced data analytics, optimized distribution channels, user-generated content incorporation, and user-centric storytelling for effective brand engagement in the modern market. This research studied the effects of distribution personalization and content decentralization on brand recall among Gen-Z, focusing on causal relationship and the issue of attention competition. It used Partial Least Squares Structural Equation Modeling to analyze 385 responses from Region III, Philippines Gen Z participants. The results indicate that personalized distribution has direct influence on brand recall through an ability to remember brand features amid consumer attention competition. Content decentralization partially mediates this effect, suggesting challenges in maintaining consistent brand identity across diverse platforms. The research underscores the importance of distribution personalization in brand recall, highlighting how content decentralization and variety of content across platforms can dilute brand consistency and hinder Gen Z's brand recall. These suggest centralizing content from a single source to ensure uniformity in branding while also using advanced analytics for targeted personalization. The study recommends optimizing distribution channels and incorporating user-centric storytelling to enhance brand association. Researchers need to continuously analyze consumer trends and feedback to refine distribution personalization strategies and stay responsive to changing market conditions. Content decentralization makes it difficult to reach and engage with the entire audience effectively, as they may be spread out across numerous channels, thus future researchers may look into this aspect.